Analisis Non Performing Loan Kredit Pemilikan Rumah Bank Persero - Rifki Khoirudin (Universitas Mercu Buana, 2021)
The purpose of this study is to analyze the factors that affect the non-performing loans for housing loans of state banks for the period 2012-2020. The use of this type of data in this research is quarterly data from the first quarter of 2012 to the fourth quarter of 2020 which is taken from various sources. This study uses secondary data sourced from the financial services authority (OJK), the Central Statistics Agency (BPS) and Bank Indonesia (BI). The analysis method used in this research is multiple regression analysis using Eviews 9 software. Based on the analysis results show that the residential property price index (IHPR) has a positive and significant effect on NPL, meaning that the increase in property prices will encourage an increase in the level of bad credit / NPL. The exchange rate has a positive and significant effect on NPL, meaning that the higher the exchange rate will increase the occurrence of bad credit / NPL. Meanwhile, income per capita and economic growth did not significantly affect non-performing loans / NPL. The R-squared value in the estimation results is 0.919662. So it can be concluded that the IHPR variable, exchange rate, economic growth and income per capita affect the NPL by 91.96%, while the remaining 8.04% is explained by other variables outside the model.